Abordagem de endometriose vesical - Leite,Tatiana Semedo (2017)
Endometriosis is not only a source of individual distress but also a burden for health care systems. Endometriosis’ prevalence remains unknown, however, it was estimated to be 6-20%, minimum. Urinary tract endometriosis (UTE) is found in 1-2% of patients with endometriosis. Bladder endometriosis (BE), defined as endometriosis infiltrating the detrusor, is relatively rare, representing 1% of all endometriosis cases and 84% of cases of urogenital endometriosis. The treatment of urinary tract endometriosis is controversial because the rarity of this condition makes randomized studies almost unfeasible. This literature review was performed to evaluate urinary tract endometriosis’ management, from diagnosis to treatment